The use of tablet and communication app for patients with endotracheal or tracheostomy tubes in the medical surgical intensive care unit: A pilot, feasibility study. - SANTIAGO, CECILIA; ROZA, DARCY; PORRETTA, KERRI; SMITH, ORLA (Canadian Journal of Critical Care Nursing)
Background: Critically ill patients commonly require endotracheal or tracheostomy tubes and mechanical ventilation for respiratory airway compromise. The use of artificial airways and mechanical ventilation prohibits traditional verbal communication. Although some mechanically ventilated patients are able to communicate through mouthing words, gesturing, or writing, many are unable to do so effectively, as a result of weakness, fatigue, or attachment to devices that restrict movement. Difficulties in communication can result in unmet needs (i.e., difficulty communicating a symptom) and communication breakdowns, which are frustrating for patients, families, and clinicians. Purpose: To explore the feasibility and usefulness of using a tablet equipped with communication app in the intensive care unit (ICU) with patients who are unable to communicate using verbal speech. Method: We conducted a pilot, observational study, approved by the local Research Ethics Board. Twenty patients with endotracheal or tracheostomy tubes were deemed eligible for the study and used the tablet equipped with an app to communicate with their bedside clinicians. A self-administered questionnaire was completed by point-of-care clinicians to determine their perspectives on the feasibility and usefulness of the tablet and communication app. Results: All patients who met eligibility criteria and consented to the study used the communication device at least once during the trial period, demonstrating its feasibility. On a scale ofO (not at all useful) to 10 (incredibly useful), 75% rated its usefulness seven or greater, mean rating of seven (range 3-10). Conclusion: The tablet equipped with a communication app is a feasible and useful device for patients and clinicians. Further exploration is needed to understand the contribution of this communication system for patients and healthcare professionals.